IL-22 Is Deleterious along with IL-17 in Allergic Asthma but Is Not Detrimental in the Comorbidity Asthma and Acute Pneumonia - Goulart, Amanda; Boko, Mèdéton Mahoussi Michaël; Martins, Nubia Sabrina; Gembre, Ana Flávia; de Oliveira, Rômulo Silva; Palma-Albornoz, Sandra Patrícia; Bertolini, Thais; Ribolla, Paulo Eduardo Martins [UNESP]; Ramalho, Leandra Naira Zambelli; Fraga-Silva, Thais Fernanda de Campos; Bonato, Vânia Luiza Deperon (MDPI, 2023)
There is evidence that IL-22 and IL-17 participate in the pathogenesis of allergic asthma. To investigate the role of IL-22, we used IL-22 deficient mice (IL-22 KO) sensitized and challenged with ovalbumin (OVA) and compared with wild type (WT) animals exposed to OVA. IL-22 KO animals exposed to OVA showed a decreased number and frequency of eosinophils, IL-5 and IL-13 in the airways, reduced mucus production and pulmonary inflammation. In addition, IL-22 KO animals exhibited a decreased percentage and number of lung CD11c+CD11b+ cells and increased apoptosis of eosinophils. Th17 cell transfer generated from IL-22 KO to animals previously sensitized and challenged with OVA caused a reduction in eosinophil frequency and number in the airways compared to animals transferred with Th17 cells generated from WT mice. Therefore, IL-22 is deleterious with concomitant secretion of IL-17. Our findings show a pro-inflammatory role for IL-22, confirmed in a model of allergen-free and allergen-specific immunotherapy. Moreover, during the comorbidity asthma and pneumonia that induces neutrophil inflammation, IL-22 was not detrimental. Our results show that targeting IL-22 would negatively affect the survival of eosinophils, reduce the expansion or migration of CD11c+CD11b+ cells, and negatively regulate allergic asthma.
Keywords: apoptosis; asthma; dendritic cell; eosinophil; IL-17; IL-22